Perspective of Agri-Environmental Service Incentives in Indonesia, Developing Countries and OECD Members - Muhammad Iqbal; Gelar Satya Budhi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
IndonesianPeran sektor pertanian di Indonesia memiliki multi fungsi terkait dengan lingkungan, ketahanan pangan, sosial ekonomi, dan budaya. Strategi utama dalam menjaga multi fungsi pertanian adalah: (a) meningkatkan kesadaran terhadap pertanian dan masyarakat pedesaan; (b) mendukung kebijakan harga pertanian; (c) meningkatkan apresiasi terhadap multi fungsi pertanian; (d) meningkatkan upaya konservasi tanah; dan (e) menentukan langkah penataan lahan sesuai dengan program revitalisasi pertanian. Kendati lahan pertanian memberikan jasa pelayanan lingkungan kepada masyarakat, namun petani tidak memperoleh insentif yang memadai dalam hal jaminan berusahatani, subsidi input, pengawasan kualitas pasokan pertanian, dan dukungan akses pasar. Oleh karena itu, gagasan insentif jasa lingkungan pertanian patut diimplementasikan. Akan tetapi, untuk kelancaran implementasi insentif jasa lingkungan pertanian tersebut perlu dilakukan terlebih dahulu analisis pemangku kepentingan diiringi dengan proyek percontohan. Dengan kata lain, beberapa langkah strategis seperti sosialisasi dan uji coba kegiatan perlu disiapkan. Modifikasi pembayaran jasa lingkungan dapat direkomendasi-kan dalam implementasi insentif jasa lingkungan pertanian di Indonesia. EnglishIndonesian agriculture has been admitted for its multifunctionality which encompasses environmental, food security, socioeconomic, and cultural roles. The main strategies to maintain the multifunctionality of agriculture are as follows: (a) improving the awareness on the agriculture and rural community; (b) providing the favorable price policy of agriculture; (c) enhancing the appreciation on the multifunctionality of agriculture; (d) improving soil conservation efforts; and (e) delineating the prime agriculture land in accordance with revitalization of agriculture, fisheries, and forestry program. Agricultural land provides environmental services to community; however, farmers deserve incentives such as secure tenure, subsidized inputs, quality control of agricultural supplies, and better market access. Hence, the notion of agri-environmental service incentives is essentially implemented. However, for better implementation, it should be initiated employing stakeholder’s analysis through a pilot project activity. In other words, there is a need that a road map strategy is implemented, including its socialization and implementation. Modified mechanism model of payment for environmental services is recommended in implementing agri-environmental service incentives in Indonesia.